Parents Experience in Providing Reproductive Health Education for Adolescent with Visual Disability in Yogyakarta - Dewi Kusumaningtyas; Budi Wahyuni; Elsi Dwi Hapsari (Faculty of Nursing, Universitas Jember, 2022)
Background: Visibility impairment in children with visual disabilities affect their cognitive experiences, reproductive health problems and sexual abuse. One way to prevent negative experiences related to reproductive health and sexuality is to reproductive health education by parents as the closest person to the child. The purpose of this research is to get an idea how parent experience in providing reproductive health education to adolescents with visual disabilities in Yogyakarta. Method: This research is a qualitative research with phenomenology approach. The study was conducted from July to August 2017 in three schools, which are: SLB Negeri I Bantul, SLB Yaketunis and MTs LB Yaketunis Yogyakarta. Participans were selected by purposive sampling based on inclusion and exclusion criterion, and considered the maximum variation sampling. The participants were 10 visual disability parents (father and/or mother). The data was collected through interviews using semi-structured interview guidelines. Data were analyzed using Colaizzi method. Result of the research: Five themes are: 1) Reproductive health education is provided in accordance with the needs of children; 2) The parents have barriers in giving reproductive health education; 3) Reproductive health education in adolescent with visual disability is given by optimizing the sense of listening, touching and kissing 4) Religion and social norms become the basis of parent’s consideration in providing reproductive health education; 5) The visual disability conditions experience by parents will affect the education provided Conclusion: Reproductive health education is important since early age in adolescents with visual disability, by considering media and appropriate methode that is by optimizing the function of the sense of hearing, touch and smell.